Molecular detection of bacterial microbome of ticks parasitizing wild boars (SUS SCROFA) in an Orang Asli community / Lim Fang Shiang - Lim, Fang Shiang (2019)
Ticks are competent hematophagous vectors of arthropod-borne diseases globally. In Malaysia, the extent of tick-borne diseases is still rarely studied and neglected. There are still many tick species from different animal hosts here in Asia region which the associated bacterial communities are unexplored. Next generation sequencing (NGS) has been used effectively recently in many studies to dissect the microbiomes of tick vectors, to reveal novel bacterial pathogen. Here, we performed a survey of the bacterial communities associated with ticks recovered from wildlife host, wild boar (n=3) trapped near forested area surrounding the Orang Asli Community. Ticks (n=72) were morphologically identified as Haemaphysalis hystricis (n=32), Dermacentor compactus (n=15), Amblyomma testudinarium (n=13), Dermacentor steini (n=10) and Dermacentor atrosignatus (n=2). Taxonomic summary of these ticks shown that there are 16 dominant bacterial taxa (relative abundance >1%), including known bacteria associated with ticks (Rickettsia, Coxiella and Francisella) and possibly environmental or skin bacteria from the sampled host (Acinetobacter, Staphylococcus). From the bacterial community analysis, it was shown that the abundance of Coxiella, Rickettsia and Francisella appeared to be associated with H. hystricis, D. compactus and D. steini tick species respectively, regardless of the hosts. Specific gene amplification was performed on selected sample to identify the Coxiella, Rickettsia and Borrelia. Sequences of spotted fever group (SFG) rickettsia were identified from 4 tick samples, with one shared high similarity to the pathogenic Rickettsia raoultii strain. A relapsing fever (RF) group Borrelia was identified from one sample, a first discovery in Malaysia. Coxiella burnetii and potential Coxiella endosymbionts were identified from ten individual samples. The iv zoonotic potential of the newly found Borrelia sp., Rickettsia sp. and Coxiella sp. merits further investigation. This study provides the baseline knowledge of the microbiome of Haemaphysalis, Dermacentor and Amblyomma ticks commonly found in parasitizing wild boar in an Orang Asli community. Further studies are required to verify if the findings here are representative of the common bacterial community of ticks in Malaysia.